The value of the humanities - Small, Helen ([The literary agenda series], 2013)
The Value of the Humanities provides a critical account of the principal arguments used to defend the value of the Humanities. The claims considered are: that the Humanities study the meaning-making practices of culture, and bring to their work a distinctive understanding of what constitutes knowledge and understanding; that, though useful to society in many ways, they remain laudably at odds with, or at a remove from, instrumental use value; that they contribute to human happiness; that they are a force for democracy; and that they are a good in themselves, to be valued 'for their own sake'. Engaging closely with contemporary literary and philosophical work in the field from the UK and US, Helen Small distinguishes between arguments that retain strong Victorian roots (Mill on happiness; Arnold on use value) and those that have developed or been substantially altered since. Unlike many works in this field, The Value of the Humanities is not a polemic or a manifesto. Its purpose is to explore the grounds for each argument, and to test its validity for the present day. Tough-minded, alert to changing historical conditions for argument and changing styles of rhetoric, it promises to sharpen the terms of the public debate.